Review of Greek and Lichhavi Numeral Systems - Acharya , Eka Ratna (Perspectives on Higher Education, 2025)
The aim of this paper is to express the review of Greek and Lichhavi numeral systems then interpret and explain the similarities and differences between these two systems. It is well known assumptions that numerals, counting system and pattern of the numerals are the most important phenomenon in mathematical approach to every scientific and social events. Here, the revisions on these numeral systems are used to explore on the basis of document analysis and historical practices. Greece and Nepal have indigenous mathematical practices with their own numeral and counting systems. In early period Greek has used Acrophonic and Alphabetical numeral systems and in context of Nepal, we have used Lichhavi numeral system. In my study I found that both of these two systems ligatures are used to form the large numbers.